Role of Lipoprotein(a) in Patients with Diabetic Chronic Renal Failure (CRF) - M. Vasanthan (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter aimed to estimate the level of lipoprotein(a) in diabetic chronic renal failure patients and to correlate with healthy controls. Chronic kidney disease, also called chronic kidney failure, involves a gradual loss of kidney function. Treatment for chronic kidney disease focuses on slowing the progression of kidney damage, usually by controlling the cause. But, even controlling the cause might not keep kidney damage from progressing. A metabolic condition with an alarming global prevalence is diabetes mellitus. If left unchecked, lipoprotein and other atherogenic variables might cause illnesses such chronic renal failure (a). A total of 60 CRF patients attending a private medical college and hospital in a sub-urban region of Chennai participated in the study. The sample size was calculated according to the prevalence of CRF in South-India. Lipoprotein(a) was estimated by immunoturbidimetric method and the other parameters by their respective methods in biochemistry auto- analyzer. The study resulted that long term glycemic control was significantly proportional to the Lp(a) concentration in controls-Group A and Group B- diabetics with CRF. This suggests that long term glycemic control is directly related to the complications of diabetes. Lp(a) inhibits binding of plasminogen (PLG) to the cell surface by accumulating in the vessel wall. It is revealed that there is a positive correlation of lipoprotein(a) levels with the duration of diabetes and was progressive with the diabetic complications. The present study observed that there is positive correlation of Lp(a) concentration with the duration of diabetes and is progressive with the diabetic complications.